WAS LUXURY LITTLE RESEARCHED? AN EXPLORATION OF STUDIES AND RESEARCH TRENDS IN THE AREA OF MARKETING OF LUXURY GOODS, BEFORE 2005 - Raluca CIORNEA; Marius D. POP; Mihai F. BACILA; Alexandra M. DRULE (TIRCA) (Management & Marketing)
The first questions that all scientists address when approaching a new domain are related to how well studied is the field, who and what has studied. The answers help them establish their personal areas of interest and contribution. Thus in order to help the authors concerned with the luxury domain we decided to conduct a secondary marketing research and the main purpose was to identify the studies and the trends in research in the area of marketing of luxury goods and their degree of approach, before 2005. The present study is only a part of a complex research that approaches the entire evolution in luxury research field, but due to space limitation papers were separated in two: the evolution before 2005 and the evolution after 2005. Unique by its theme, this paper is intended to be ambitious by analysing all the luxury materials to which had access the authors The results confirmed the previous statement of some authors that luxury was little researched comparing to other domains.